SEM Model to Assess the Impact of Mobile Gaming on Islamic Education Learning - Fuadiy, Moch. Rizal; Rozi, M. Asep Fathur; Marpuah, Siti (Journal of Educational Research and Practice, 2024)
This study examines the impact of mobile gaming on Islamic Religious Education (Indonesian: PAI) learning outcomes using Structural Equation Modeling (SEM). Conducted at Madrasah Aliyah Negeri (MAN) 1 Tulungagung, the research utilized surveys and documentation for data collection. Analysis, carried out with JASP software, began with Explanatory Factor Analysis (EFA) to uncover data structures, followed by Confirmatory Factor Analysis (CFA) to validate these structures. The findings indicate that excessive mobile gaming negatively affects PAI learning outcomes, whereas positive perceptions of gaming are associated with improved academic performance. The SEM analysis reveals intricate relationships among gaming activity, student perceptions, and learning outcomes, suggesting that while gaming can boost engagement, it may also hinder academic focus if not managed appropriately. The study further explores how motivation and engagement with specific game genres—such as MOBA, Battle Royale, and RPG—might differentially influence PAI learning outcomes. However, the current SEM analysis does not directly address these genre-specific effects, highlighting the need for additional research. In conclusion, the study emphasizes the necessity of balanced integration of mobile gaming in educational contexts and provides practical recommendations for educators and policymakers to navigate these challenges effectively.